(3EOGQI GdCYeGd GdMchejI (B:s (3GdfXQjGJ hGdYedjGJ hGdehGQO (B/s - (3eMeO , ehab MOjOs (.(3YeGf(B: s (3OGQ GdefGgL(B, s, 2002)
(3GdGWGQ GdfXQj ddGOGQI GdYGeI, BdjI GdGOGQI GdYGeI(B: (3gjcdI hJUeje GdCLgRI GdMchejI, OjfGejcjI GdGOGQI GdYGeI (B: (3GdYedjGJ h eeGQSI GdhXGFa GdGOGQjI aj GdefXeGJ GdMchejI , ehGQO GdGOGQI GdYGeI h eSJbHdgG(B.s
(3eQGLY U(B.487s
Keywords: (3GdGOGQIs; (3GdGOGQI GdYGeIs